Komunikasi Sebagai Proses Simbolik: Studi Literatur - Erwan Efendi; Muhammad Yusuf Kamala; Maya Arianti (Journal on Education, 2023)
Communication is a symbolic process, one of the basic human needs, symbolization or the use of symbols. Therefore, this study aims to find out that communication is a symbolic process, one of the basic human needs, symbolization or use of symbols, content and space for communication, and communication taking place in various levels of gaps. This study used a qualitative approach with library research and content analysis techniques. The result of this research is that communication is used to channel information and a meaning through certain media according to the situation.